Meaning and morality : essays on the philosophy of Julius Kovesi - Tapper, Alan.; Mooney, T. Brian. (Studies in Moral Philosophy, 2012)
Julius Kovesi's Moral Notions (1967) was a startlingly original contribution to moral philosophy and theory of meaning. After initial positive reviews Kovesi's book was largely forgotten. Nevertheless, it continued to have an enduring influence on a number of philosophers and theologians some of whom have contributed to this volume. The original essays collected here critique, analyze, deepen and extend the work of Kovesi. The book will be of particular interest to moral philosophers and those working on concept formation, while also having a broader appeal to social scientists grappling with the description/evaluation problem.